Preparation method of honeycomb-shaped titanium nitride ceramic aerogel
Through the mixing of hydrothermal method and organic sol, combined with supercritical drying and carbon thermal reduction nitriding method, ultralight TiN ceramic aerogel with honeycomb structure was prepared, which solved the problems of high sintering temperature and high production cost of existing TiN porous ceramic materials, and achieved high porosity, low thermal conductivity and excellent mechanical properties of the material.
Patent Information
- Application Number
- CN202411828980.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing TiN porous ceramic materials have problems such as high sintering temperature, high production cost, poor purity and low porosity, and are difficult to effectively apply in high temperature, high pressure and corrosive environments.
TiO2 nanorods were prepared by hydrothermal method, and then mixed with an organic sol, and ultralight TiN ceramic aerogel with a honeycomb structure was prepared by sol gel, supercritical drying, and carbon thermal reduction and nitriding.
The prepared honeycomb TiN ceramic aerogel has a large specific surface area, low thermal conductivity, excellent mechanical properties, thermal insulation properties and oxidation resistance, which improves its mechanical strength and high temperature oxidation resistance in an aerobic environment.
Smart Images

Figure CN119751077A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of preparation technology of aerogel materials, and relates to a method for preparing honeycomb titanium nitride (TiN) ceramic aerogel. Background technology:
[0002] Aerogel material is a three-dimensional lightweight porous material composed of nanoparticles or polymer molecular chains. It has attracted widespread attention in high-temperature insulation applications due to its high temperature resistance and low thermal conductivity. However, traditional oxide aerogels have many weaknesses, such as insufficient thermal stability, easy phase transition and particle sintering. In contrast, nitride materials have high melting point, high hardness, high thermal stability and wear resistance, making them suitable for extreme application conditions of high temperature, high pressure and corrosive environment. Among them, TiN porous ceramic materials have attracted widespread attention due to their excellent high temperature resistance, high strength and high thermal insulation properties, but the current TiN porous ceramics face challenges such as high sintering temperature, high production cost, poor purity and low porosity. Zhang Shaowei et al. from Wuhan University of Science and Technology (Han L, Dong L, Zhang H, et al. Journal of the European Ceramic Society, 2021, 41(10): 5127-5137) used TiO2 and chitosan powder as starting materials and prepared TiN aerogel by freeze casting and carbon thermal reduction nitridation. However, the specific surface area of TiN aerogel prepared by this method is too small, only 80 to 167 m 2 / g, and the thermal conductivity at room temperature is as high as about 0.1W / (m K), and this preparation method is relatively complicated, the preparation process has high energy consumption, and it is not easy to mass produce. Rao Huashang et al. from South China Agricultural University (Cheng, Qi, Zhouhong Yin, Zhenxiao Pan, et al. ACS Applied Energy Materials, 2021, 4 (8): 7599-7610.) used tetrabutyl titanate and graphene oxide as raw materials, and prepared graphene oxide / TiN aerogel by freeze drying and carbon thermal reduction nitridation, but this method is costly, the preparation process is complicated, and it is not easy to industrialize. Huang Shuangneng et al. (CN202410574363.X) directly added metal catalysts and carbon sources to TiO2 aerogel, and prepared titanium carbonitride aerogel by carbonitridation treatment, but the specific surface area of the titanium carbonitride aerogel obtained by this method was only 358.7m 2 / g, and its operation is complicated and not suitable for large-scale production. Summary of the invention:
[0003] The purpose of the present invention is to improve the deficiencies of the prior art and provide a method for preparing a honeycomb titanium nitride ceramic aerogel. First, TiO2 nanorods are prepared by a hydrothermal method, and then mixed with an organic sol. A new method for preparing an ultralight TiN ceramic aerogel with a honeycomb structure is obtained by sol-gel, supercritical drying, and carbon thermal reduction nitridation. The prepared honeycomb TiN ceramic aerogel has a large BET specific surface area and a very low thermal conductivity, and exhibits excellent mechanical properties, thermal insulation properties, and oxidation resistance, and improves its mechanical strength and high temperature oxidation resistance in an aerobic environment.
[0004] The specific technical solution of the present invention is: a method for preparing honeycomb titanium nitride ceramic aerogel, and the specific steps are as follows:
[0005] (1) mixing a titanium source, water, and an acid in a certain molar ratio at 20 to 30° C., and obtaining TiO2 nanorods through a hydrothermal reaction and oven drying;
[0006] (2) mixing phenol, aldehyde, sodium carbonate and water in a certain molar ratio at 20 to 30° C. and stirring to obtain an organosol;
[0007] (3) mixing the TiO2 nanorods obtained in step (1) and the organosol obtained in step (2) at a certain mass ratio at 20 to 30°C and stirring them uniformly, placing them at 50 to 100°C for 12 to 72 hours to allow the gel to age, and then performing solvent replacement;
[0008] (4) subjecting the wet gel obtained in step (3) to supercritical carbon dioxide drying to obtain a precursor aerogel;
[0009] (5) The precursor aerogel obtained in step (4) is heat-treated under a nitrogen atmosphere to obtain a honeycomb titanium nitride TiN ceramic aerogel.
[0010] Preferably, the acid in step (1) is one or a mixture of hydrochloric acid, sulfuric acid, phosphoric acid, boric acid or oxalic acid; the mass concentration of the acid is 5-50%; the titanium source is one or a mixture of tetrabutyl titanate, n-propyl titanate, n-butyl titanate or ethyl titanate; the titanium source, water and acid are mixed in a molar ratio of 1: (10-20): (30-40); the temperature of the hydrothermal reaction is 150-300° C., and the time of the hydrothermal reaction is 1-5 h; the temperature of the oven drying is 40-60° C., and the drying time is 12-72 h.
[0011] Preferably, the phenol in step (2) is one or a mixture of catechol, resorcinol, hydroquinone, cresol or pyrogallol; the aldehyde is one or a mixture of formaldehyde, acetaldehyde, butyraldehyde, cinnamaldehyde or anisaldehyde; wherein the phenol, aldehyde, sodium carbonate and water are mixed in a molar ratio of 1:(2-6):(0.1-0.8):(1-5).
[0012] Preferably, in step (3), the TiO2 nanorods and the organic sol are uniformly mixed in a mass ratio of 1: (0.1-0.8); the replacement solvent is one or a mixture of ethanol, methanol, acetone, n-pentanol or isopropanol; the number of replacements is 5-15 times, with an interval of 6-12 hours between each time.
[0013] Preferably, the carbon dioxide supercritical drying in step (4) uses carbon dioxide as the drying medium, the drying temperature is 40-70° C., the drying pressure is 8-15 MPa, the degassing rate is 4-16 L / min, and the drying time is 5-14 h.
[0014] Preferably, the heat treatment temperature in step (5) is 1000-1500° C., the heating rate is 2-8° C. / min, and the holding time is 2-5 h.
[0015] Beneficial effects:
[0016] The method of the present invention and the method for preparing a honeycomb TiN ceramic aerogel prepared by the method have the following characteristics:
[0017] (1) The preparation process of the invention is simple, the raw materials are easily obtained, the energy consumption is low, the efficiency is high, the cost is low, and large-scale production is possible.
[0018] (2) The invention provides a method for preparing a honeycomb TiN ceramic aerogel, which has the characteristics of low thermal conductivity, high porosity, high specific surface area, and strong antioxidant properties. Description of the drawings:
[0019] Figure 1 This is a sample picture of the honeycomb TiN ceramic aerogel obtained in Example 1 before and after the 1300°C butane spray gun experiment.
[0020] Figure 2 This is the X-ray diffraction pattern of the honeycomb TiN ceramic aerogel obtained in Example 2.
[0021] Figure 3 This is a scanning electron microscope image of the honeycomb TiN ceramic aerogel obtained in Example 3. Specific implementation method:
[0022] The present invention is further described below with reference to examples, but the protection scope is not limited thereto.
[0023] Example 1
[0024] Tetrabutyl titanate, water, and hydrochloric acid (5wt%) were mixed and stirred at a molar ratio of 1:10:30 at 20°C, and then hydrothermally treated at 150°C for 5h, and then placed in an oven at 40°C for 72h to obtain TiO2 nanorods. Then catechol, formaldehyde, sodium carbonate, and water were mixed and stirred at a molar ratio of 1:2:0.1:1 at 20°C to obtain an organic sol. TiO2 nanorods and organic sol were mixed and stirred at a mass ratio of 1:0.1 at 20°C, and then placed at 50°C for 72h to gel, and then replaced with ethanol solvent, where the replacement times were 5 times, each time with an interval of 12h. The wet gel was subjected to supercritical carbon dioxide drying to obtain a precursor aerogel, where the drying temperature was 40°C, the drying pressure was 8MPa, the degassing rate was 4L / min, and the drying time was 14h. Finally, the obtained precursor aerogel was heat treated in a nitrogen atmosphere, wherein the heat treatment temperature was 1000°C, the heating rate was 2°C / min, and the holding time was 5h. Figure 1 This is a sample picture of the prepared honeycomb TiN ceramic aerogel before and after the 1300℃ butane spray gun test. As can be seen from the figure, the shape of the aerogel remains unchanged after the 1300℃ butane spray gun test, without any shrinkage or cracks. After characterization and testing, the aerogel is a pure phase TiN ceramic aerogel material, and its specific surface area is as high as 515.5m2 / g, and the thermal conductivity at room temperature is only 0.048W / (m·K). The material was characterized by scanning electron microscopy, and it was found that the sample was obviously honeycomb-shaped and had a uniform pore structure, which is beneficial to improving the thermal insulation performance of the material.
[0025] Example 2
[0026] Titanate n-propyl, water, and sulfuric acid (10wt%) were mixed and stirred at a molar ratio of 1:20:40 at 25°C, and then hydrothermally treated at 300°C for 1h, and then placed in an oven at 45°C for 48h to obtain TiO2 nanorods. Then, resorcinol, acetaldehyde, sodium carbonate, and water were mixed and stirred at a molar ratio of 1:6:0.8:5 at 25°C to obtain an organic sol. TiO2 nanorods and organic sol were mixed and stirred at a mass ratio of 1:0.8 at 25°C, and placed at 100°C for 12h to gel, and then replaced with methanol solvent, wherein the replacement times were 12 times, and each time was 6h apart. The wet gel was subjected to carbon dioxide supercritical drying to obtain a precursor aerogel, wherein the drying temperature was 70°C, the drying pressure was 15MPa, the degassing rate was 16L / min, and the drying time was 5h. Finally, the obtained precursor aerogel was heat treated in a nitrogen atmosphere at a temperature of 1500°C, a heating rate of 8°C / min, and a holding time of 2h. The prepared honeycomb TiN ceramic aerogel remained unchanged in shape after being tested by a butane spray gun at 1300°C, without any shrinkage or cracks. Figure 2 The X-ray diffraction diagram of the prepared honeycomb TiN ceramic aerogel shows that its diffraction peak is consistent with the TiN standard spectrum, proving that the sample is a pure phase TiN ceramic aerogel material. After characterization and testing, the specific surface area of the material is as high as 513.8m 2 / g, and its thermal conductivity at room temperature is only 0.051W / (m·K). When the material was characterized using a scanning electron microscope, it was found that the sample was obviously honeycomb-shaped and had a uniform pore structure, which is beneficial to improving the thermal insulation performance of the material.
[0027] Example 3
[0028] The n-butyl titanate, water and phosphoric acid (50wt%) were mixed and stirred at 30℃ in a molar ratio of 1:12:38, and then hydrothermally treated at 200℃ for 4h, and then placed in a 50℃ oven for 36h to obtain TiO2 nanorods. Then, hydroquinone, butyraldehyde, sodium carbonate and water were mixed and stirred at 30℃ in a molar ratio of 1:3:0.2:3 to obtain an organosol. TiO2 nanorods and organosol were mixed and stirred at 30℃ in a mass ratio of 1:0.3, and placed at 60℃ for 48h to gel, and then acetone solvent was replaced, wherein the replacement times were 8 times, and each time was 9h. The wet gel was subjected to carbon dioxide supercritical drying to obtain a precursor aerogel, wherein the drying temperature was 50℃, the drying pressure was 10MPa, the degassing rate was 8L / min, and the drying time was 12h. Finally, the obtained precursor aerogel was heat treated in a nitrogen atmosphere, wherein the heat treatment temperature was 1200°C, the heating rate was 4°C / min, and the holding time was 4h. The prepared honeycomb TiN ceramic aerogel remained unchanged in shape after being tested by a 1300°C butane spray gun, without any shrinkage or cracks. After characterization and testing, the aerogel was a pure phase TiN ceramic aerogel material, and its specific surface area was as high as 515.6m2 / g, and the thermal conductivity at room temperature was only 0.046W / (m·K). Figure 3 This is a scanning electron microscope image of the honeycomb TiN ceramic aerogel. It can be seen from the image that the sample is obviously honeycomb-shaped and has a uniform pore structure, which is beneficial to improving the thermal insulation performance of the material.
[0029] Example 4
[0030] Titanate ethyl, water, and boric acid (20wt%) were mixed and stirred at 35°C in a molar ratio of 1:15:32, and then hydrothermally treated at 250°C for 2h, and then placed in a 55°C oven for 24h to obtain TiO2 nanorods. Then, cresol, cinnamaldehyde, sodium carbonate, and water were mixed and stirred at a molar ratio of 1:4:0.6:2 at 35°C to obtain an organic sol. TiO2 nanorods and organic sol were mixed and stirred at 35°C in a mass ratio of 1:0.6, and placed at 80°C for 36h to gel, and then replaced with n-pentanol solvent, wherein the replacement number was 9 times, and each interval was 8h. The wet gel was subjected to carbon dioxide supercritical drying to obtain a precursor aerogel, wherein the drying temperature was 60°C, the drying pressure was 12MPa, the degassing rate was 10L / min, and the drying time was 7h. Finally, the obtained precursor aerogel was heat treated in a nitrogen atmosphere, wherein the heat treatment temperature was 1300℃, the heating rate was 5℃ / min, and the holding time was 3.5h. The prepared honeycomb TiN ceramic aerogel remained unchanged in shape after being tested by a 1300℃ butane spray gun, without any shrinkage or cracks. After characterization and testing, the aerogel was a pure phase TiN ceramic aerogel material, and its specific surface area was as high as 514.7m2 / g, and its thermal conductivity at room temperature was only 0.050W / (m·K). The material was characterized by scanning electron microscopy, and it was found that the sample was obviously honeycomb-shaped and had a uniform pore structure, which was beneficial to improving the thermal insulation performance of the material.
[0031] Example 5
[0032] Tetrabutyl titanate, water, and oxalic acid (30wt%) were mixed and stirred at 40°C in a molar ratio of 1:18:35, and then hydrothermally treated at 280°C for 3h, and then placed in a 60°C oven for 12h to obtain TiO2 nanorods. Then, pyrogallol, anisaldehyde, sodium carbonate, and water were mixed and stirred at 40°C in a molar ratio of 1:5:0.5:4 to obtain an organic sol. TiO2 nanorods and organic sol were mixed and stirred at 40°C in a mass ratio of 1:0.5, and then placed at 90°C for 24h to gel, and then replaced with isopropanol solvent, wherein the replacement number was 10 times, and each time was 7h apart. The wet gel was subjected to carbon dioxide supercritical drying to obtain a precursor aerogel, wherein the drying temperature was 55°C, the drying pressure was 13MPa, the degassing rate was 14L / min, and the drying time was 9h. Finally, the obtained precursor aerogel was heat treated in a nitrogen atmosphere, wherein the heat treatment temperature was 1400℃, the heating rate was 6℃ / min, and the holding time was 3h. The prepared honeycomb TiN ceramic aerogel remained unchanged in shape after being tested by a 1300℃ butane spray gun, without any shrinkage or cracks. After characterization and testing, the aerogel was a pure phase TiN ceramic aerogel material, and its specific surface area was as high as 514.7m2 / g, and its thermal conductivity at room temperature was only 0.047W / (m·K). The material was characterized by scanning electron microscopy, and it was found that the sample was obviously honeycomb-shaped and had a uniform pore structure, which was beneficial to improving the thermal insulation performance of the material.
Claims
1. A method for preparing a honeycomb titanium nitride ceramic aerogel, the specific steps of which are as follows: (1) mixing a titanium source, water, and an acid in a certain molar ratio at 20 to 30° C., and obtaining TiO2 nanorods through a hydrothermal reaction and oven drying; (2) mixing phenol, aldehyde, sodium carbonate and water in a certain molar ratio at 20 to 30° C. and stirring to obtain an organosol; (3) mixing the TiO2 nanorods obtained in step (1) and the organosol obtained in step (2) at a certain mass ratio at 20 to 30°C and stirring them uniformly, placing them at 50 to 100°C for 12 to 72 hours to allow the gel to age, and then performing solvent replacement; (4) subjecting the wet gel obtained in step (3) to supercritical carbon dioxide drying to obtain a precursor aerogel; (5) The precursor aerogel obtained in step (4) is heat-treated under a nitrogen atmosphere to obtain a honeycomb titanium nitride TiN ceramic aerogel.
2. The preparation method according to claim 1, characterized in that The acid in step (1) is one or a mixture of hydrochloric acid, sulfuric acid, phosphoric acid, boric acid or oxalic acid; the mass concentration of the acid is 5-50%; the titanium source is one or a mixture of tetrabutyl titanate, n-propyl titanate, n-butyl titanate or ethyl titanate; the titanium source, water and acid are mixed in a molar ratio of 1: (10-20): (30-40); the temperature of the hydrothermal reaction is 150-300° C., and the time of the hydrothermal reaction is 1-5 hours; the temperature of the oven drying is 40-60° C., and the drying time is 12-72 hours.
3. The preparation method according to claim 1, characterized in that The phenol in step (2) is one or a mixture of catechol, resorcinol, hydroquinone, cresol or pyrogallol; the aldehyde is one or a mixture of formaldehyde, acetaldehyde, butyraldehyde, cinnamaldehyde or anisaldehyde; wherein the phenol, aldehyde, sodium carbonate and water are mixed in a molar ratio of 1:(2-6):(0.1-0.8):(1-5).
4. The preparation method according to claim 1, characterized in that In step (3), the TiO2 nanorods and the organic sol are uniformly mixed in a mass ratio of 1: (0.1-0.8); the replacement solvent is one or a mixture of ethanol, methanol, acetone, n-pentanol or isopropanol; the number of replacements is 5-15 times, with an interval of 6-12 hours between each replacement.
5. The preparation method according to claim 1, characterized in that The carbon dioxide supercritical drying in step (4) uses carbon dioxide as a drying medium, with a drying temperature of 40 to 70° C., a drying pressure of 8 to 15 MPa, a degassing rate of 4 to 16 L / min, and a drying time of 5 to 14 h.
6. The preparation method according to claim 1, characterized in that The heat treatment temperature in step (5) is 1000-1500° C., the heating rate is 2-8° C. / min, and the insulation time is 2-5 h.
Citation Information
Patent Citations
Preparation method of blocky titanium carbide, titanium nitride or titanium carbonitride aerogel
CN111892420A
Microporous material / carbon aerogel composite material as well as preparation method and application thereof
CN114669275A
Preparation method of titanium nitride aerogel
CN115849314A
Preparation method of biomass-based titanium nitride ceramic aerogel
CN118684499A
Method for preparing bulk c-aln composite aerogel with high strength and high temperature resistance
US20150108389A1